2009
DOI: 10.1016/j.jasms.2009.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization quadrupole ion-mobility time-of-flight mass spectrometry as a tool to distinguish the lot-to-lot heterogeneity in N-glycosylation profile of the therapeutic monoclonal antibody trastuzumab

Abstract: Monoclonal antibodies are typically glycosylated at asparagine residues in the Fc domain, and glycosylation heterogeneity at the Fc sites is well known. This paper presents a method for rapid analysis of glycosylation profile of the therapeutic monoclonal antibody trastuzumab from different production batches using electrospray quadrupole ion-mobility time-of-flight mass spectrometry (ESI-Q-IM-TOF). The global glycosylation profile for each production batch was obtained by a fast LC-MS analysis, and comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 50 publications
(59 reference statements)
6
102
0
Order By: Relevance
“…As described in previous work, the assignments were confirmed by activating in parallel all species dispersed on the time dimension by the ion mobility element, before transfer to the mass analyzer (Quinn et al 2013). Called time aligned parallel (TAP) dissociation (Damen et al 2009;Castro-Perez et al 2011), this technique provided extensive fragmentation data that matched those observed for the yeast extract in the LTQ-orbitrap determinations. In addition, we explored an alternative characterization strategy that mimicked more traditional tandem MS spectrometry by fragmenting only those species that were recognized as potential PTMs.…”
Section: Assignment Confirmationmentioning
confidence: 82%
“…As described in previous work, the assignments were confirmed by activating in parallel all species dispersed on the time dimension by the ion mobility element, before transfer to the mass analyzer (Quinn et al 2013). Called time aligned parallel (TAP) dissociation (Damen et al 2009;Castro-Perez et al 2011), this technique provided extensive fragmentation data that matched those observed for the yeast extract in the LTQ-orbitrap determinations. In addition, we explored an alternative characterization strategy that mimicked more traditional tandem MS spectrometry by fragmenting only those species that were recognized as potential PTMs.…”
Section: Assignment Confirmationmentioning
confidence: 82%
“…Several studies of large proteins, protein complexes, and protein therapeutics have incorporated IM-MS or CIU IM-MS to determine CCS values [23,[30][31][32][34][35][36][37][38]; however, the suitability of this technique to compare and differentiate protein therapeutics has not yet been evaluated. In this work, we evaluated the suitability of IM-MS and CIU IM-MS measurements for analysis of protein therapeutic systems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, characterization of therapeutic mAbs by MS has been applied to product and process development 13,14 and batch consistency assessment. 15 However, MS still needs to be used in concomitance with orthogonal analytical techniques to be able to focus on the different facets of the protein including mainly liquid chromatography (LC). [16][17][18][19][20][21][22] Recently, we described a method using capillary zone electrophoresis (CZE) coupled to tandem MS with a sheathless interface to perform the simultaneous characterization of several aspects of a protein in one injection, including AA sequence and posttranslational modifications (PTMs).…”
Section: Introductionmentioning
confidence: 99%